THE «PLEA BARGAINING» IN HUNGARY - Gácsi, Anett Erzsébet (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Aim: the main task of this scientific research is to study the ’plea bargaining’ in the Hungarian criminal proceedings. Methods of research: the using of international literature and the practice of Hungarian criminal judges. Results: the possible solutions to look at by the Hungarian legislator during the codification works in the quest of expediting proceedings and making them more efficient, included for example the legal institution of plea bargaining working excellently in the American continent and the amicable settlement type proceedings conducted in Europe. As a result, the new legislation has established the rules for cooperation by the defendant and the framework within which they should be applied. When establishing the system of cooperation based on the defendant’s confessing testimony, the legislator took into consideration the failure of the separate proceeding titled ’waiver of right to trial’. The establishment of the defendant cooperation forms and their complex system (which, in some points, resembles the solution applied in the French model) was, in part, a response to that failure. Discussion: based on the comparison of the main international legal literature.